Human pulpal response to direct pulp capping with an adhesive system - Pereira, J. C.; Segala, A. D.; Costa, CAS (Mosher & Linder, Inc, 2000)
Purpose: To evaluate clinically and microscopically the human pulp response when directly capped with an adhesive system or calcium hydroxide over short (9-12 days) and long (53-204 days) experimental periods. Materials and Methods: Fifty-one sound human premolars scheduled for orthodontic extraction, had their pulp horns gently exposed with a diamond point. Debris in the pulp wound was washed out with a sterile saline solution. The pulps were then capped with either an adhesive system (Scotchbond Multi-Purpose Plus) or calcium hydroxide. All teeth were subsequently restored with resin-based composite (Z-100) according to the manufacturer's instructions. After the experimental periods, the teeth were extracted and processed for light microscopic examination. Results: Short-term: the pulp tissue capped with SBMP-P exhibited dilated and congested blood vessels associated with a mo;derate inflammatory response and blanching of pulp cell nuclei. Long-term: no evidence of healing and bridge formation was observed. A persistent mild inflammatory pulp response was present. Micro-abscesses were detected in three cases associated with bacterial infiltration. Calcium hydroxide stimulated early pulp repair and dentin bridging which extended into the longest period.